2014
DOI: 10.1149/2.0281410jes
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Effect of Non-Uniform Current Density on the Performance of Soluble Lead Redox Flow Batteries

Abstract: Soluble lead acid redox flow battery (SLRFB) offers a number of advantages. These advantages can be harnessed after problems associated with buildup of active material on electrodes (residue) are resolved. A mathematical model is developed to understand residue formation in SLRFB. The model incorporates fluid flow, ion transport, electrode reactions, and non-uniform current distribution on electrode surfaces. A number of limiting cases are studied to conclude that ion transport and electrode reaction on anode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…With regards to the soluble lead RFB (SLRFB), a number of issues have to be addressed before it can be commercialised, 92 such as low charge efficiency 53 and incomplete dissolution of active solids (Pb on the cathode and PbO 2 on the anode), which can accumulate during charge-discharge cycling. Aer a few charge-discharge cycles, the accumulated residue on the electrodes begins to disintegrate and PbO 2 /PbO particles entrain in the electrolyte, resulting in an irreversible loss of the active material that leads to the formation of an insulating layer deep inside the PbO 2 deposits at high acid concentrations.…”
Section: Soluble Lead Redox Batterymentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to the soluble lead RFB (SLRFB), a number of issues have to be addressed before it can be commercialised, 92 such as low charge efficiency 53 and incomplete dissolution of active solids (Pb on the cathode and PbO 2 on the anode), which can accumulate during charge-discharge cycling. Aer a few charge-discharge cycles, the accumulated residue on the electrodes begins to disintegrate and PbO 2 /PbO particles entrain in the electrolyte, resulting in an irreversible loss of the active material that leads to the formation of an insulating layer deep inside the PbO 2 deposits at high acid concentrations.…”
Section: Soluble Lead Redox Batterymentioning
confidence: 99%
“…Hence, the previous modelling studies on SLRFB have provided insights into two step charging 95 and effects of temperature, species concentrations 96 and electrode morphology 97 on battery performance. 53 One of these models accounts for ion transport resistance for electron transfer reactions using Butler-Volmer kinetics with tted values of rate constants and non-uniform deposition on electrodes by simulating non-uniform current densities on the electrodes. 53 The model is simulated using COMSOL® for a SLRFB with planar electrodes using fast reaction kinetics, slow reaction kinetics and low transport resistance in the concentration boundary layer.…”
Section: Soluble Lead Redox Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…Another mathematical model for this system incorporates the current distribution to study a number of limiting cases. The authors concluded that the anodic reaction and the ion transport controlled the battery performance [327]. Current distribution for other systems such as the Zn-ferricyanide [328], the all-iron flow battery [264] and the vanadium RFBs [234,305] propose different mathematical models.…”
Section: Operational Engineering and Design Aspects 81 Reactor Designmentioning
confidence: 99%
“…Experimental work partially validated the simulation and showed a close resemblance to the model results.Nandanwar and Kumar have created two models of the SLFB. The first[84] is a two-dimensional model that uses the same standard governing equations for an electrochemical system. The model is able to simulate charge/discharge behaviour, including non-uniform current distribution on the electrode surface, and the effect of flow rate and flow direction.…”
mentioning
confidence: 99%